VOCABULARY DEVELOPMENT IN CHILDREN AGE 18 – 24 MONTHS - Oktadela, Resy (Universitas PGRI Sumatera Barat, 2017)
This paper aims at describing the first language acquired by the children in age 18 - 24 months. This period can be said as at the beginning point when children starting to produce words in their life. The data were taken from a baby 19 months’ years old, named Elpon, he lives in Trivana Regency, PekanBaru Province. The method is by using diary to note the vocabularies have been acquired.